1997
DOI: 10.1007/978-1-4471-0967-9
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Nonlinear Control

Abstract: In this book several streams of nonlinear control theory are merged and directed towards a constructive solution of the feedback stabilization problem. Analytic, geometric and asymptotic concepts are assembled as design tools for a wide variety of nonlinear phenomena and structures. Differential-geometric concepts reveal important structural properties of nonlinear systems, but allow no margin for modeling errors. To overcome this deficiency, we combine them with analytic concepts of passivity, optimality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
1,113
0
32

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,695 publications
(1,153 citation statements)
references
References 66 publications
8
1,113
0
32
Order By: Relevance
“…P Since the derived control law does not rely on exact cancellation of the system nonlinearity f , intuition tells us that it should possess some robustness properties. This can be confirmed using the inverse optimality tools of (Sepulchre et al, 1997). It can be shown that for the system (13), the backstepping control law (18) minimizes the cost functional…”
Section: A Generic Backstepping Designmentioning
confidence: 64%
“…P Since the derived control law does not rely on exact cancellation of the system nonlinearity f , intuition tells us that it should possess some robustness properties. This can be confirmed using the inverse optimality tools of (Sepulchre et al, 1997). It can be shown that for the system (13), the backstepping control law (18) minimizes the cost functional…”
Section: A Generic Backstepping Designmentioning
confidence: 64%
“…In general, to prove that an operator is (relaxed) co-coercive, it is possible to use a storage function approach assuming zero initial conditions (the interested reader is referred to the references [14] and [15]). Consider one of the systems in (17) and suppose that there exists a scalar function S (called incremental storage function) such that for every two input-output pairs σ 1 , y 1 and σ 2 , y 2 ,…”
Section: State Space Formalismmentioning
confidence: 99%
“…We now aim to write incremental dissipation inequalities satisfied by the incremental subsystems of the CFSs and refer the reader to [14], [15] for comprehensive treatments of passivity and the more general concept of dissipativity. We will show that in general these inequalities will be such that these subsystems are incrementally output semipassive: that is, they are incrementally output passive outside a ball centered on the origin |Πy i | = 0.…”
Section: B Incremental Systems and Incremental Storage Functionsmentioning
confidence: 99%